Thy-1, a Pathfinder Protein for the Post-genomic Era - Morris, Roger J. (Frontiers in Cell and Developmental Biology, 2018)
Abstract: a wealth of molecular detail is rapidly emerging to demonstrate that Thy-1, a small lipid-anchored cell surface protein expressed at sharply defined differentiation stages on a variety of tissues of ectodermal, mesodermal and endodermal origin, is a ligand for a number of integrin and other receptors, whose signaling efficiency is modified by Thy-1 to direct differentiation within developing tissues, or in the case of the brain, to stabilize adult signaling networks. Thy-1 and its receptor are usually on different cells, interacting in trans, fulfilling both adhesive and signaling functions in which the engagement of Thy-1 with its receptor alters signaling in both cells. Here I review aspects of the cell biology of Thy-1, and studies of its role as deduced from gene knock-out studies, that suggest how this protein can participate in so many different signaling-related functions.